Analysis of a Flux-Concentrated V-Type Biased-Flux Slot Motor - Mohammad Amirkhani; Ehsan Farmahini Farahani; Mohammad Afrank; Mojtaba Mirsalim; Nick J. Baker (IEEE Access)
Biased flux motors are a configuration of electrical machine where the rotor is pure iron and magnets are buried in the stator yoke iron. In this paper, a biased-flux motor is proposed and validated in which the stator coreback permanent magnets are configured to a flux concentrating V-type arrangement. By switching from the more usual circumferential magnets, it has been shown that torque production per unit magnet mass can increase by over 20% for a moderate 0.5% increase in torque ripple. This is by virtue of the significant increase in flux concentration in the air gap, which is proven mathematically, via simulation and validated experimentally. It is also shown that due to the new permanent magnet shape, demagnetization is limited. A comprehensive comparison is done to show the superiority of the proposed structure. Finally, validation of the theoretical and FEM analyses has been done experimentally by a prototyped 24/25 V-type motor.